Apurinic/apyrimidinic endonuclease 1 is associated with poor prognosis after curative resection followed by adjuvant chemotherapy in patients with stage III colon cancer - Ji Hyeong Song; Myung Sun Lee; Eun Young Cha; Kyung Ha Lee; Ji Yeon Kim; Jin Soo Kim (Korean Journal of Clinical Oncology, 2022)
Purpose Apurinic/apyrimidinic endonuclease 1 (APE1) is a key enzyme involved in the base excision repair pathway. It also has redox activity and maintains various transcription factors in an active reduced state. APE1 may be associated with chemoresistance. In the present study, we first investigated the expression level of APE1 protein and its correlation with oncologic outcomes of oxaliplatin-based chemotherapy in patients with stage III colon cancer. Further, we investigated the effects of human APE1 siRNA on the sensitivity of oxaliplatin in SNU-C2A colon cancer cells. Methods Tissue specimens from tumor and normal colon of 33 patients with stage III colon cancer were obtained from 2006 to 2009. The patients received at least eight cycles of oxaliplatin-based chemotherapy. APE1 expression was analyzed by immunohistochemistry and Western blotting using a cultured SNU-C2A cell line. Cell viability and apoptosis were determined by Cell Counting Kit-8 and caspase-3 cleavage using Western blotting. Results All the colon cancer tissues showed APE1 staining in the nucleus, whereas all the normal colon tissues were negative for APE1 staining in the cytoplasm. The group with a higher expression of APE1 demonstrated poorer prognosis than the group with low expression (P=0.026 for overall survival and P=0.021 for disease-free survival). Treatment with oxaliplatin resulted in a dose-dependent increase in APE1 expression in SNU-C2A cells. APE1 siRNA significantly enhanced oxaliplatin-induced growth inhibition, and also increased oxaliplatin-induced apoptosis in SNU-C2A cells. Conclusion APE1 could be considered a prognostic factor in colon cancer patients treated with oxaliplatin-based chemotherapy.